Lead effect on the morphophysiology of leaves and roots of Peltophorum dubium (Spreng.) Taub., a potential phytostabilizer - da Silva Paiva, W. [UNESP]; de Araujo, M. A. [UNESP]; Rosalem, P. F. [UNESP]; Ferreira, T. C. [UNESP]; Bomfim, N. C.P. [UNESP]; Gonçalves, R. A. [UNESP]; Martins, A. R. [UNESP]; de Camargos, L. S. [UNESP] (Springer Nature, 2024)
Lead (Pb) can be found in metallic, organic, or inorganic forms, having no function in plant metabolism. This work aimed to evaluate the performance of Peltophorum dubium (Spreng.) Taub., an arboreal legume native to South America, in soils contaminated with Pb, based on the analysis of morphophysiological modifications in its leaves and roots, its tolerance index, and its vegetative growth. The experiment was conducted under a completely randomized design, in a greenhouse, using four treatments, namely the control (without lead) and three lead concentrations (100, 300, and 500 mg/kg soil−1), each treatment consisting of five replicates. The fresh and dry weight of leaves, stem, and root and the Tolerance Index for Pb were measured at the end of the experiment. Concerning the leaf anatomy, the thickness of the adaxial epidermis, abaxial epidermis, the palisade and spongy parenchyma, and the total thickness of the leaflets were analyzed. The cross-section vessel element area was evaluated in the root. Nitrate, soluble proteins, and ureides were evaluated in leaves and roots. There was an increase in the thickness of the abaxial epidermis, in the palisade and spongy parenchyma, and the total thickness of the leaflets, and a decrease in the root cross-section vessel element area. The leaves showed an increase in the concentrations of soluble compounds, while the roots showed a decrease in the concentration of these compounds. The species presents a tolerance index superior to 0.7 for all treatments, having survived even at the concentration of 500 mg Pb dm−3.
Keywords: Heavy metals; Morphophysiology; N compounds; Pb toxicity; Peltophorum dubium; Tolerance index